UTILIZING RASCH ANALYSIS TO ANALYZE AND IDENTIFY STUDENTS’ ATTITUDE TOWARD ECONOMICS - Komala, Ida; Umar, Fini Alfionita; Kunaedi, Jajang (STKIP Persada Khatulistiwa Sintang, 2023)
Economics is one of the subjects studied in class 10th grade of high school. Demand, supply, and the balance of market prices are material that contains many mathematical symbols, curves, and graphs that are learned in grade 10. One that influences the enthusiasm of students in learning economics is their attitude towards economics. This study aims to identify students’ attitudes towards economic learning after the COVID-19 period by utilizing Rasch analysis approach. The sample of this study was 81 high school students in Subang consisting of 61 female students and 20 male students. This research method uses a quantitative method with a survey design, especially using a cross-sectional design. Students’ attitudes towards the economy were identified using an instrument of 15 statements in the form of a Likert scale. The results of the analysis show that 77% of students have a positive attitude and 23% of students have a negative attitude towards the economy. So it can be concluded that the attitude of students towards the economy, especially in terms of demand , supply, and market equilibrium tends to be positive